PENGARUH MANAJEMEN STRATEGIK TERHADAP UPAYA PENCAPAIAN VISI DI SMA DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI - Muhammad Nasih; Wulan Novia Sari (IAI Darussalam, 2020)
The objectives of this study are as follows: (1) to determine the Strategic Management of SMA Darussalam Blokagung tegalsari Banyuwangi 2019-2020 Academic Year (2) To find out the efforts to achieve the Vision of the Darussalam Darussalam Tegalsari Banyuwangi High School 2019-2020 academic year (3) To determine the effect Strategic management of efforts to achieve the vision of Darussalam Darussalam Blokagung Tegalsari Banyuwangi School Year 2019-2020.The data collection methods used in this study are questionnaires, observations, documentation. As for testing the validity of the data using the Bivariate Correlations formula, to find the reliability of data using the Cornbach Alpha formula. Then for hypothesis testing using the f test and t test, for the normality test using the Kolmogrov-Smirnovc formula. In the analysis of data using simple linear regression analysis. The population in this study was 35 teachers from SMA Darussalam. The results of this study indicate that: (1) the strategic management implemented by the Darussalam High School in Blokagung Tegalsari Banyuwangi in the 2019-2020 academic year is classified as good, due to the t-test. 10,708> 2,042 t tables, which means that Ha is accepted; (2) shows that the efforts to achieve the vision applied by the Darussalam High School Blokagung Tegalsari Banyuwangi in the 2019-2020 academic year are classified as good because t count 10.708> 2.042 t tables which means that Ha is received; (3) The effect of strategic management on efforts to achieve vision is known to be 79.8% while the remaining 20.2% is influenced by other variables which means the influence of strategic management on efforts to achieve vision in SMA Darussalam Tegalsari Banyuwangi 2019-2020 Learning Year is good.